The mixing of solid waste from palm acid oil and palm kernel cake as a source of animal feed (free range chicken) - Ali Zainal-Abidin, Mohamad Termizi; Muhammad Amirul Syafiq, Nasarudin; Nurul Farah Anisa, Hairolnizam; Farah Amalina, Ishak; Abdul Syukor, Abd Razak; Suryati, Sulaiman (2022)
Today, waste and waste management has given rise to many pressing issues. Waste management is a crucial area related to the economic status of a country and the lifestyle of its population. Wastewater pollution from high production of palm oil results in high production of palm oil mill effluent (POME) is a main problem throughout the world. This study is to analyze palm oil waste characteristics in making of the formulated chicken feed. Therefore, this study also focuses on the chicken feed formulation production by the mixture of palm acid oil (PAO) and palm kernel cake (PKC). This study also to investigate the growth rate of chicken towards the formulation of the chicken feed. In experiment, free range chickens were used and divided into 2 groups with different formulation which are Diet 1 (D1) and Diet 2 (D2). The chicken was fed with the formulation continuously for 5 months (free-range chicken). The result obtained from Diet 2 (D2) was recorded and compared with Diet 1 (D1) which are control diet.